PERBEDAAN ASUPAN MAKRO MINERAL DAN STATUS GIZI BERDASARKAN KEJADIAN NYERI HAID PADA REMAJA PUTRI - Ni Desak Made Evi Anggaraeni; I Ketut Kencana; I Made Purnadhibrata (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Menstrual pain is pain that occurs mainly in the lower abdomen, which can spread to the lower back, waist, pelvis, upper thighs, until the calf. One that influences menstrual pain is intake. Macro mineral intake such as calcium and magnesium is very important in managing menstrual pain. Besides nutritional status also affects the occurrence of menstrual pain. This study aims to determine the differences in macro mineral intake and nutritional status based on the incidence of menstrual pain in adolescent girls in Senior High School 2 Tabanan. This type of research is an observational study with a cross-sectional design. The sample size in this study was 66 students at Senior High School 2 Tabanan. Variables are collected through research instruments. The results showed there were 57 samples (86.4%) with calcium intake in the less category, 17 samples (25.8%) with magnesium intake in the less category, 55 samples (83.3%) with good nutritional status, and 53 samples (80.3%) had pain menstruation. From the analysis using an independent t-test showed that there was no difference in calcium intake between students who experience menstrual pain and no menstrual pain (p value = 0.431), there was no difference in magnesium intake between students who experienced menstrual pain and did not experience menstrual pain. (p value = 0.538), and there was no difference in nutritional status between students who experienced menstrual pain and did not experience menstrual pain (p value = 0.601). Keywords : breakfast, energy consumption and nutritional status